Method for maintaining adult solitary bee Centris analis under laboratory conditions - Tadei, Rafaela [UNESP]; da Silva, Cláudia Inês; Decio, Pâmela; Silva-Zacarin, Elaine C. M.; Malaspina, Osmar [UNESP] (Wiley, 2022)
Although solitary bees represent at least 70% of bee species, most ecotoxicological studies on bees focus on social species and there are only a few species of solitary bees. One of the challenges in developing toxicological studies on solitary bees is the lack of protocols for maintaining these species under laboratory conditions. This study aimed to develop a method to maintain adult individuals of the solitary bee Centris analis under controlled conditions. Six models of cages with adaptations for food identification and resting areas were tested based on cages used for Apis mellifera and Osmia bicornis. With this in mind, we placed one individual of Centris analis in each cage and set the temperature at 28°C. Cage models with survival higher than 50% of individuals were used to measure the influence of photoperiod, training and concentration of food in bee adaptation and longevity. Cages containing a wood cube and an artificial fabric flower supported the survival of 75% of captive bees for longer than 30 days at 28°C. Bee survival rate was higher in the absence of photoperiod. This work showed the importance of an acclimatization period of 3 days for C. analis and described a feasible method for future studies evaluating the effects of pesticide effects on solitary bees under laboratory conditions.
Keywords: Brazilian bees; cages; native bee; pesticides; solitary bee